Difference influence of rubbing and soaking tooth extraction instruments in 70% alcohol on total oral bacterial colonisation on clinical students at the Department of Oral Surgery and Maxilofacial March-May 2018 - Ahyar Riza; Hendry Rusdy; Isnandar Isnandar; Evelin N. Sari (DiscoverSys Inc., 2020)
Objective: To compare the effect of rubbing and soaking tooth extraction instrument in 70% Â alcohol on total oral bacterial colonisation at the Department of Oral Surgery, Faculty of Dentistry, Universitas Sumatera Utara.Â Material and Methods: This is an experimental research with a post-test only approach. The sampling technique used is Purposive Sampling. In this study, sample were divided into 2 groups consisting of 18 extraction instruments which are lower molar forceps rubbed with 70% alcohol and soaked in 70% alcohol. Each instrument were pre-cleaned using brush, water and soap prior disinfection process.Results: The results were statistically analyzed using Mann-Whitney Test. The result showed no significant difference to the total bacteria count on rubbing and soaking using 70% alcohol.Conclusion: Soaking in 70% alcohol method showed more effective because it overally kills bacteria.Keyword:Â